A Proposed Framework for the Adoption of the Fourth Industrial Revolution Technologies in Municipal Water Governance in South Africa - CLARITY HUTETE; Shikha VYAS-DOORGAPERSAD; Nqobile SIKHOSANA (Journal of Digital Food, Energy & Water Systems)
The Sustainable Development Goal 6 (SDG 6), which focuses on ensuring universal access to water for all, remains at the center of the sustainable development agenda; however, its realisation continues to be hindered by the persistent water governance challenges. This is particularly concerning given the critical role that effective governance plays in addressing the global water crisis. The advent of Fourth Industrial Revolution (4IR) technologies offers transformative potential to strengthen municipal water governance systems. Yet, the adoption and implementation of these technologies, especially within South African rural municipalities, has been notably slow. Using a selected district municipality in the Eastern Cape in South Africa, the paper aims to develop a framework to facilitate the adoption of 4IR technologies in municipal water governance. Adopting a qualitative research approach, the study purposively selected participants from the municipal officials, stakeholders, and experts who provided insights into the challenges and opportunities associated with 4IR adoption. Data were collected through semi-structured interviews and analysed thematically. The findings reveal a slow uptake of 4IR innovations, underpinned by capacity, infrastructure, and policy gaps. The paper, therefore, proposes a contextually grounded framework designed to guide and accelerate digital transformation within rural municipalities.  Thus, the framework provides a roadmap and direction in accelerating the integration of 4IR technologies to strengthen municipal water governance, foster inclusive technological advancement, and ensure that rural communities are not excluded from the benefits of digital innovation. The paper, therefore, underscores the urgency of this shift by highlighting that the Fourth Industrial Revolution (4IR) is rapidly transforming all sectors. Consequently, the failure of rural water service authorities to adopt 4IR technologies risks deepening existing disparities and leaving rural municipalities further behind.